ANALISIS PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA MENGENDARAI MOBIL KARENA KELALAIANNYA DAPAT MENYEBABKAN KEMATIAN DAN KERUSAKAN PADA KENDARAAN ATAU BARANG LAIN (Studi Putusan Nomor : 8/ Pid-Sus /2022/ PN-Met) - M. Faisol Rizka; Dwi Doni Prasetiyo; Erlina B; Zainab Ompu Jainah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
A traffic accident is an unexpected and unwanted event that is difficult to predict when and where it occurs in road traffic. involves the use of a vehicle by a person with or without other road users which causes injury, trauma, disability or death to the person driving it. Many factors, including a lack of public awareness about motorized vehicle drivers, are responsible for the high rate of traffic accidents. Analysis of the liability of criminals driving cars because their negligence can cause death (Decision Study Number 8/ Pid-Sus /2022/ PN-Met), is the problem of this research. This research uses both normative and empirical juridical approaches. The research results show that perpetrators who drive motorized vehicles are responsible for their mistakes which cause traffic accidents with fatalities and damage to vehicles or goods. Decision Number 8/Pid.Sus/2022/PN Met claims that the defendant Irzun Ramadhani Bin Ujang Niat has been legally and convincingly proven guilty of committing the offense and charges the defendant above with a prison sentence of one year; determines that the time of detention and detention of the defendant has been deducted from the sentence imposed; decided that the defendant must remain in detention, and required the defendant to pay court costs of Rp. 2,000.00.